Intermittent hypobaric hypoxia and neuroendocrine reaction of the parvocellular neurons of the paraventricular hypothalamic nucleus - V. O. Shamenko; Ye. V. Kadzharian; A. V. Abramov (Zaporozhye State Medical University, 2019)
The neuroendocrine system occupies an important place in the systemic mechanisms of the body response to stress. The paraventricular nuclei of the hypothalamus (PVH) are one of the most important links of the brain`s neuroendocrine system which determine the reactivity of the hypothalamic-pituitary-adrenal axis (HPA) in response to the various stressors and thereby ensure the development of adaptive reactions by the formation of body resistance to the stress. The aim of the research was to study the functional state of the peptidergic neurons of the medial parvocellular nuclei of the paraventricular hypothalamic nucleus (PVHmp) during the multi-day action of intermittent hypobaric hypoxia and in the posthypoxic period. Materials and methods. The research was conducted on 24 male Wistar rats. Intermittent hypoxia was modeled by a daily 6-hour stay of rats at an altitude of 6000 m (pO2 = 9.8 %) for 15 days, the posthypoxic period lasted for 10 days. The distribution of corticotropin-releasing hormone (CRH), [Arg8]-vasopressin (AVP), β-endorphin, cFos and HIF-1α proteins was studied by quantitative immunofluorescence methods in serial frontal sections of the hypothalamus. Results. The intermittent hypobaric hypoxia stimulated the developing of mild hypertrophy of PVHmp neurons and increased the concentration of RNA in the cytoplasm by 37 %. An indicator of PVHmp neurons response to hypoxia was 2.5-fold increase in the concentration of the HIF-1α protein in them. IHH elevated the concentration of cFos protein in PVHmp by 37 %, increased the area of immunoreactivity to AVP by 2.5 times, to CRH and β-endorphin by 3 times. There was an increase in the synthesis of neuropeptides in response to hypoxia, which led to the elevation in the concentration of AVP in PVHmp by 6.6 times, β-endorphin by 7 times, and CRH by 8.5 times. The immunoreactivity indicators for the HIF-1α protein and its concentration in PVHmp remained at a high level in the posthypoxic period. At the same time, high immunoreactivity to CRH and β-endorphin in PVHmp was noted, as well as a high concentration of these neuropeptides in neurons against the background of AVP synthesis inhibition in neurons. It is possible that high rates of neurosecretory activity of PVHmp in the posthypoxic period may indicate the formation of neuroendocrine mechanisms of adaptation of the HPA axis to the long-term effect of hypoxia. Conclusions. Intermittent hypobaric hypoxia stimulates the neurosecretory activity of the PVHmp neurons, increases the synthesis and secretion of CRH and AVP hormones that activate the HPA axis. Synthesis of the secretory response indicator cFos protein and a central regulator of hypoxic responses HIF‑1α protein is also increasing in the peptidergic neurons of the PVHmp. High levels of the PVHmp neurosecretory activity at the posthypoxic period are preserved and indicate the formation of neuroendocrine mechanisms of the HPA axis adaptation to the long term intermittent hypoxia exposures.